Urbanization as a Historical Vindication Device for the Right to the City in Santiago of Chile (1930-1950) - Prudant-Soto, E (UNIV PASSO FUNDO, 2023)
The article analyzes the claims for urbanization of inhabitants of certain suburban neighborhoods of Santiago between 1930 and 1950, as an expression of a process of appropriation of their inhabited space and resistance to the dynamics of inequality characteristic of metropolitan development in Latin America. To this end, the demands inscribed in the significant concept of dignity on part of neighborhood-based associations are examined. Likewise, the political dimension of associativism and affirmation practices emerged from the periphery rooting for the "right to the city" are addressed. As the main historical sources, the paper analyzes a set of small newspapers produced and circulated in various neighborhoods on the outskirts of Santiago, allowing us to study how the working classes that suffered from urban problems fought against spatial segregation